(untitled) (Eurasian Journal of Ecology, 2024)
The relevance of the research topic is explained by the increased risk of spring floods in the Akmola region, the significant damage they cause to the local economy and the need to develop and implement effective measures to prevent them. The purpose of this study is to develop a proper assessment of the environmental risk of spring floods and their consequences on the territory of the Akmola region, which is important for regional enterprises. The methodological approach includes a systematic analysis of the probability of occurrence of various environmental risks from spring floods in combination with the study of patterns of development of negative consequences of these floods in the region and in the Republic of Kazakhstan as a whole. As part of the current study, results have been identified that indicate the serious consequences of spring floods for economic activity in areas that were flooded during seasonal floodwaters, as well as the need to develop and implement specific measures to prevent spring floods caused by significant violations of economic activity in the water protection zone. The results obtained during the study, as well as the scientific conclusions derived from them, are significant for agricultural workers in the Akmola region who feel the irreversible effects of spring floods when carrying out their activities in the region, as well as for residents of these areas who regularly encounter the described difficult natural situations. Keywords: natural disaster; ecology; flooding; seasonal flooding of reservoirs; economic activity.